2021
DOI: 10.1038/s41598-020-80350-w
|View full text |Cite
|
Sign up to set email alerts
|

Three-year outcomes of vitrectomy combined with intraoperative dexamethasone implantation for non-tractional refractory diabetic macular edema

Abstract: This retrospective, consecutive interventional study investigated the long-term clinical outcomes of combined vitrectomy with intraoperative dexamethasone implants for non-tractional refractory diabetic macular edema (DME). The study included 43 eyes from 39 participants with DME that had continued for more than 6 months despite repeated non-surgical treatment. Postoperative changes in best-corrected visual acuity (BCVA) and central macular thickness (CMT) were evaluated over 3 years. A Kaplan–Meier curve was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the removal of ERM may increase the drug penetration into the retina after intravitreal injections [7,8]. A beneficial effect of ILM peeling during vitrectomy for RVO has also been correlated with decompression of the edematous retina [30], even though ILM peeling was not found to be significantly associated with treatment outcomes in our cohort.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the removal of ERM may increase the drug penetration into the retina after intravitreal injections [7,8]. A beneficial effect of ILM peeling during vitrectomy for RVO has also been correlated with decompression of the edematous retina [30], even though ILM peeling was not found to be significantly associated with treatment outcomes in our cohort.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have examined the outcomes of secondary ERM surgical removal in eyes with tractional diabetic macular edema, reporting good anatomical and variable functional results [7,8]. In addition, pars plana vitrectomy (PPV) has been proven effective in ERM due to uveitis or trauma [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent DME refractory to various non-surgical treatments can be challenging to treat and manage 17 , 18 . A previous study reported that TelCap was associated with chronic macular edema refractory to intravitreal treatment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…While some studies show that patients with refractory DME would benefit with vitrectomy [26], other studies have shown no significant visual improvement with ILM peeling although there may be anatomical improvement [27,28]. Addition of intravitreal steroid along with ILM peeling in some cases of refractory DME, has shown to improve visual outcome in longterm [29].…”
Section: Vitrectomy In Tractional Versus Non-tractional Dmementioning
confidence: 99%